Aerodynamics and flight stability analysis of a 3D printed UAV - Tan, Tracy Wen Chee (2017)
With the rise of 3D printing and Unmanned Aerial Vehicles (UAVs), more and more projects are researching on 3D printed UAVs. With cheaper and smaller 3D printer, 3D printing UAVs at home will be a trend in the near future. While UAVs are common, flying wing UAVs are not common and well researched to be functional. Therefore, this report will look into a 3D printed flying UAV to provide two objectives. First, to compile a quick and simple performance analysis procedure with an open-source software, XFLR5. This section will include full design alteration analysis in XFLR5 to improvement lateral stability, looking into the dihedral layout and winglet area increment. The analysis will be base on Dutch roll damping ratio, yawing moment damping ratio and the root locus graph. The whole of the first section aims to allow online purchase and self-printing of 3D printed UAVs easy and giving guide to personalization of UAVs. Cross comparison with the wind tunnel testing of the model will also be included to discuss on the reliability of XFLR5. Second, determining which of the two possible 3D printing directions will produce a better performance UAV and thus will be the suggested printing direction given to people who would 3D print their UAVs. The models were printed in two extreme directions 90° to each other and put through wind tunnel testing. The coefficients of lift will be used for comparison and giving the final verdict.